Psychological Capital and Turnover Intention: The Mediating Role of Burnout among Employees - Abdinegara, Renno Pandu; Radikun, Tulus Budi (Dinasti International Journal of Management Science, 2026)
High turnover intention remains a persistent challenge for organizations operating in high-demand work environments due to its adverse consequences for performance, service quality, and human resource sustainability (Hom et al., 2017). Drawing on Job Demands–Resources (JD–R) theory, this study examines the effect of psychological capital on turnover intention through burnout as a mediating mechanism (Bakker & Demerouti, 2017). Using a quantitative cross-sectional design, data were collected from 110 employees in a service-oriented organization in Indonesia. Psychological capital was measured using the Psychological Capital Questionnaire (PCQ-12), burnout was assessed with the Oldenburg Burnout Inventory (OLBI), and turnover intention was measured using the Turnover Intention Scale (TIS-6) (Luthans et al., 2015; Demerouti et al., 2010; Bothma & Roodt, 2013). Data were analyzed using descriptive statistics, correlation analysis, and mediation analysis with Jamovi. The results indicate that psychological capital has a significant negative effect on burnout, burnout has a significant positive effect on turnover intention, and burnout fully mediates the relationship between psychological capital and turnover intention. These findings extend JD–R theory by clarifying the mechanism through which personal resources reduce withdrawal intentions and offer practical implications for human resource management in high-demand organizations.